Alloreactive T-cell clones transformed by Theileria parva retain cytolytic activity and antigen specificity - Baldwin, Cynthia L.; Teale, A.J. (Wiley, 1987)
Theileria parva is a protozoan parasite which infects and transforms bovine lymphocytes. This study examined the effects of Theileria‐induced transformation on phenotype and function, in terms of cytolytic potency and specificity, of class I and class II‐specific alloreactive T cell clones. Alloreactive T cell clones infected with T. parva (Muguga) retained expression of the T cell differentiation antigens BoT2, BoT4, BoT8 and the mature T cell antigen recognized by monoclonal antibody ILA27, as well as cytolytic function and antigen specificity, over a period of 3–4 months in continuous culture. These features were identical to those expressed by the uninfected parent clones. During this period, neither antigenic stimulation nor exogenous growth factors were required for the maintenance of proliferation, function or antigen specificity. Thereafter, cytolytic activity declined and was eventually lost, which may reflect degenerative changes normally associated with T cell senescence rather than result from parasitization per se.